Competition and Pricing in the Credit Card Market - Stango, Victor (The Review of Economics and Statistics, 2000)
Many credit card issuers charge “fixed rates” that remain the same for three to five years, while the rest charge “variable rates” that are indexed to market rates. The presence of these two distinct rate types forces prices at firms selling an otherwise identical product to move asynchronously; variable rates move one-for-one with the index, while fixed rates stay constant. Empirical and theoretical analysis shows that this pricing structure provides an explanation for the simultaneous (yet seemingly contradictory) existence of high rate-cost margins and aggressive non-price competition for new customers, a phenomenon that existed in the credit card market in the early 1990s.